CYBERBULLYING. THE ISSUE OF SECURITY IN THE ONLINE ENVIRONMENT IN THE AGE OF DIGITIZATION - TOLBARU, Carmina-Elena (International Journal of Legal and Social Order, 2025)
The paper addresses the phenomenon of cyberbullying as an emerging form of digital violence in the context of accelerating digitalization processes and the extensive use of information technologies. The analysis is carried out from an interdisciplinary perspective – psychological, sociological, legal and technological –, focusing on defining characteristics of online bullying (repetitiveness, anonymity, power imbalance) and its disproportionate impact on victims. The study investigates behavioral typologies, gender and age differences, as well as the relationship between cyberbullying and traditional forms of bullying. From a legal point of view, the research highlights the gaps in the Romanian legislative framework, analyzing in parallel the European standards and the recent jurisprudence of the European Court of Human Rights (the cases Buturugă v. Romania, Volodina v. Russia, M.Ș.D. v. Romania). The findings show the need for an autonomous criminalization of cyberbullying, as well as the adaptation of criminal legislation and public policies to the new digital realities. In this regard, the paper formulates integrated reform proposals – legislative measures, educational and social programs, technological solutions based on artificial intelligence and inter-institutional cooperation mechanisms – with the aim of strengthening the protection of victims and reducing the incidence of the phenomenon. The conclusion underlines the need for a coherent national and European approach, in which legal instruments are complemented by digital education, social responsibility and the active involvement of online platforms in preventing and combating cyberbullying.